G. R. Driver’s Contribution to Neb’s Translation of Psalms 51–100 - Clackson, Ben (The journal of theological studies, 2021)
The influence of G. R. Driver on the translation of the Old Testament in The New English Bible has been controversial particularly in light of Barr’s critique of his use of comparative philology. This article takes a sample of 18 instances of translations of verses in Psalms 51-100 which reflected proposals made in his articles. It explains the proposals, examines their influence on recent Hebrew lexicography, and shows which proposals were subsequently dropped in Psalms: a New Translation for Worship or The Revised English Bible, in order to reassess which proposals have stood the test of time. It is concluded that about half of Driver’s proposals still seem probable, which suggests that wholesale rejection of Driver’s work is unwarranted.